IMPACT OF CLIMATE CHANGE AND RAPID URBANISATION ON THE ENVIRONMENTAL AND AGRICULTURAL SECTOR OF BHUTAN (International Journal of Food and Nutritional Sciences, 2023)
Bhutan is located on the Tibetan Plateau's southern edge. Like the other plateaus, theTibetan plateau is also suffering from climate change. Since the year 2000, temperatures atBhutan's 24 weather stations have risen by about 1 °C in summer and 2 °C in winter. From2010 to 2039, the average annual temperature in Bhutan is anticipated to increase by 1 °C.